2005
DOI: 10.19182/remvt.9925
|View full text |Cite
|
Sign up to set email alerts
|

Enquête sérologique de la brucellose bovine au Cameroun

Abstract: A partir d’août 2002 jusqu’à juillet 2003, une enquête sérologique a été conduite à l’abattoir de Dschang (Ouest Cameroun) afin de déterminer la prévalence de la brucellose bovine. Huit cent quarante sérums bovins ont été examinés par l’Elisa indirect (iElisa) et le test au rose bengale (TRB). La séroprévalence de la brucellose a été de 9,64 et 4,88 p. 100 en utilisant respectivement l’iElisa et le TRB. Quatre-vingt et un sérums positifs avec iElisa et 50 sérums sélectionnés aléatoirement parmi les sérums qui … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
2
2
1
Order By: Relevance
“…Lower seroprevalence was also reported by Ojong [ 17 ] (4.6%) using RBPT in indigenous cattle in Northwest region. The finding of this study is close to the report of Shey-Njila et al [ 11 ] (9.64%) who used indirect ELISA in indigenous cattle in the Western Highlands Regions. However, Bornarel and Akakpo [ 37 ] found a brucellosis seroprevalence of 12.5% in the Northern Cameroon and several other studies have reported brucellosis seroprevalence ranging from 7 to 31% [37, 38, 39, 40, 41, 42].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Lower seroprevalence was also reported by Ojong [ 17 ] (4.6%) using RBPT in indigenous cattle in Northwest region. The finding of this study is close to the report of Shey-Njila et al [ 11 ] (9.64%) who used indirect ELISA in indigenous cattle in the Western Highlands Regions. However, Bornarel and Akakpo [ 37 ] found a brucellosis seroprevalence of 12.5% in the Northern Cameroon and several other studies have reported brucellosis seroprevalence ranging from 7 to 31% [37, 38, 39, 40, 41, 42].…”
Section: Discussionsupporting
confidence: 90%
“…Ibrahim et al [ 7 ] and Boukary et al [ 38 ] have reported that transhumance animals were major risk factor for brucellosis in sedentary animals and that the prevalence of brucellosis increased in sedentary herds that share same environments (pasture, water points, shelter) with animals on transhumance. In conformity with the seroprevalence rates reported in various parts of Africa [ 1 , 3 , 34 , 35 , 38 , 40 , 45 , 46 ], previous works have observed higher rates in the more humid (4.6–9.6%) [ 9 , 11 , 17 ] than dryer (3%) [ 18 ] regions of Cameroon. However, the reason for higher individual seroprevalence rates recorded in regions with dry climates such as Mali [ 47 ], Burkina Faso [ 48 ], and Algeria [ 49 ] is not clear.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The slaughter of predominantly mature cattle may have overestimated the seroprevalence of brucellosis in the current study. Higher abattoir prevalence rates than in the current study have been reported in Nigeria (3.9%) [ 46 ], Tanzania (4.7%) [ 47 ] and several African countries [ 48–54 ] where the vaccination of cattle against brucellosis is limited to absent. The proportion of brucellosis infected cattle farms identified at the abattoir (9.6%) was low, and similar to the prevalence of infected farms (9.3%) reported previously in Namibia [ 26 ], which is an endorsement of the effectiveness of brucellosis control measures implemented in the country.…”
Section: Performance Of Test Assayscontrasting
confidence: 47%